Эпоха бедствий: роман / А. Мартьянов - Мартьянов Андрей (Мир Волкодава, 2000)
Экземпляры: АБ (20170620) / Инвентарный номер: 33889 / Цена: 42.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 29 / ББК: 84(2Рос=Рус)6